PENGARUH JOB INSECURITY TERHADAP TURNOVER INTENTION PADA KARYAWAN RUMAH SAKIT UMUM X DI MEDAN - Sinarsi Meliala; Indo Mora Siregar; Dwi Nursiti; Tri Utami Waruwu (JURNAL PSYCHOMUTIARA, 2020)
Human resources are an important factor in a company. The discharge of employees from a company will result in a considerable impact. Employee turnover is always the main problem faced by organizations without considering the location, size, nature of the business, and business strategy. The high level of employee turnover can be seen from the amount of shifting desire that employees have in a company. Turnover is a form of end-effort of employees who experience job insecurity. This study aims to determine the effect of job insecurity on turnover intention on employees of General Hospital X in Medan. This study involved 72 permanent employees of Medan General Hospital X with a minimum of one year of service. Data was obtained through two scales, namely the job insecurity scale and turnover intention scale. The results of regression analysis showed that job insecurity had a positive and significant effect on turnover intention for employees of General Hospital X Medan. Job insecurity became one of the predictors of turnover intention with a contribution of 12.9%. The implications of this research are expected To the company to evaluate and approach employees that they (employees) are needed to work in the company, employees need to be given support in working in the company in the form of opportunities to experience self-improvement / development, meeting the needs accordingly with work, training to grow or exclude and develop creativity in work, equip superiors with the ability to guide (mentoring), skills in interproductive relationships, and effective abilities in problem solving, good decision making, communication and negotiation that do not injure rights or self individual (employee).